Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ma15030797
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Studies of Tetracycline Antibiotics on Hydroxyapatite (001) Surface—A First-Principles Insight

Abstract: Owing to the limitations of traditional systemic drug delivery in the treatment of bone diseases with side effects on normal cells, the selection of materials with high affinities for bones, as targeting ligands to modify drug carriers, has become an important research topic. Tetracyclines (TCs) have an adsorption effect on hydroxyapatite (HAp). Thus, they can be used as bone-targeting ligands and combined with drug carriers. In this study, density functional theory is used to analyze the interaction mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The nature and chemistry of the HA control the interaction with biomolecules, and the surface chemistry and porosity are fundamental variables. The interaction between adsorbed molecules and hydroxyapatite surfaces is predominantly Van der Waals forces, hydrogen, and weak coordination bonds [78].…”
Section: Functionalization By Physical Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature and chemistry of the HA control the interaction with biomolecules, and the surface chemistry and porosity are fundamental variables. The interaction between adsorbed molecules and hydroxyapatite surfaces is predominantly Van der Waals forces, hydrogen, and weak coordination bonds [78].…”
Section: Functionalization By Physical Adsorptionmentioning
confidence: 99%
“…Other fluoroquinolones, such as enoxacin, have been employed together with nano-HA/Polyurethane-cement to enhance the antibacterial properties of bone cement [109]. Adsorption has been used to introduce broadspectrum antibiotics of the tetracycline class and cyclic oligosaccharides, such as cyclodextrin, onto HA surfaces [78,88,95]. Moreover, antibiotics from the glycopeptides class as vancomycin has been loaded into porous substrates to obtain a controlled release [84,91].…”
Section: Functionalization By Antibacterial Compositesmentioning
confidence: 99%
“…Some mineral-based therapies have been demonstrated to accomplish new bone formation by downregulating the osteoclast activity. The nano-hydroxyapatite (nano-HA) crystal further has the potential to combat osteoporosis as reported in in vivo study suggesting its role in initiating bone formation to the point of healing [85].…”
Section: Nanotherapeutics For Osteoporosismentioning
confidence: 99%
“…Therefore, use of this antibiotic was discontinued in paediatric regimens. Song et al [85] have reported the targeting mechanisms for tetracycline and its derivative to HA surface and resolved the issues of the nonspecific binding to bone in an in vitro model, but it has not been validated in any biological model as yet [92]. Unlike tetracycline, bisphosphonates have emerged as attractive targeting molecules in recent years, as they are widely used due to their strong affinity to bind with HA and can be exploited in the treatment of osteoporosis and bone osteolytic disease.…”
Section: Nanotherapeutics For Osteoporosismentioning
confidence: 99%
“…The development of scaffolds for the regeneration of bone defects has been a major research target in the orthopedic field in the last decades, especially given the steady rise of traumas or metabolic diseases such as osteoporosis and bone tumors (Sohn and Oh, 2019;Reid, 2020;Zhao et al, 2021). Biomaterials based on calcium phosphates and hydroxyapatite (HA), are widely considered as elective for the development of bone scaffolds, due to their high chemical similarity with the mineral phase of bone tissue, which is a key aspect to promote new bone formation (Jeong et al, 2019;Lodoso-Torrecilla et al, 2021;Tavoni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%